2020
DOI: 10.1080/21501203.2020.1816584
|View full text |Cite|
|
Sign up to set email alerts
|

Antioxidant, antimicrobial and neuroprotective effects of Octaviania asterosperma in vitro

Abstract: Octaviania asterosperma: (hypogeous Basidiomycota) We investigated the phenolic composition, and antioxidant, antimicrobial and antigenotoxic effects of methanol extracts of fruiting bodies from Octaviania asterosperma. The total phenolic content (ppm) of O. asterosperma was found to be catechin (54.73 ± 4.68), epicatechin (123.90 ± 8.52), caffeic acid (4.23 ± 0.97), phydroxybenzoic acid (37.72 ± 3.84), cinnamic acid (58.07 ± 5.40), gallic acid (56.64 ± 6.39), clorogenic acid (80.76 ± 4.92) and coumaric acid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 76 publications
(85 reference statements)
0
14
0
Order By: Relevance
“…The differences among the TAS values for the abovementioned fungus species may be attributed to the potential of these species to produce different antioxidant compounds and the differences in the environments in which they grow. It was also found that the ethanolic extract of H. myxotricha mycelia grown in SDB and GPY media had significantly lower TOS (1.320 μmol/l) and OSI (0.024) values than those for previously studied fungi species such as M. procera (TOS: 6.596 and 10.349 μmol/l, OSI: 0.235 and 0.367) (Akgül et al, 2016 ), O. olearius (TOS: 14.210 μmol/l, OSI: 0.503) (Sevindik et al, 2017 ), A. auricula (TOS: 23.910 μmol/l, OSI: 2.367) , T. versicolor (TOS: 17.760 μmol/l, OSI: 2.166) (Akgül et al, 2017 ), D. quercina (TOS: 6.868 μmol/l, OSI: 2.201) , I. hispidus (TOS: 6.534 μmol/l, OSI: 0.224) , F. fomentarius (TOS: 2.601 μmol/l, OSI: 0.080) , F. torulosa (TOS: 2.969 μmol/l, OSI: 0.074) , T. gibbosa (TOS: 3.522 μmol/l, OSI: 0.597) , T. biforme (TOS: 4.356 μmol/l, OSI: 0.543) (Bal et al, 2017 ), C. unicolor (TOS: 19.308 μmol/l, OSI: 0.288) (Sevindik, 2018b ), G. lividus (TOS: 13.465 μmol/l, OSI: 0.651) (Bal, 2018 ), L. tigrinus (TOS: 19.294 μmol/l, OSI: 1.106) (Sevindik, 2018a ), C. cylindracea (TOS: 21.109 μmol/l, OSI: 0.488) (Sevindik et al, 2018a ), P. limonella (TOS: 4.742 and 33.022 μmol/l, OSI: 0.199 and 1.459) (Sevindik et al, 2018b ), L. sulphureus (TOS: 19.294 μmol/l, OSI: 1.106) (Sevindik et al, 2018c ), C. varius (TOS: 14.358 μmol/l, OSI: 0.627) (Sevindik, 2019 ), C. cibarius (TOS: 6.380 μmol/l, OSI: 0.121) (Sevindik, 2019 a), G. lucidum (TOS: 10.177 μmol/l, OSI: 0.185) (Bal, 2019 ) , L. nuda (TOS: 36.920 μmol/l, OSI: 1.190) (Bal et al, 2019 a), I. geotropa (TOS: 30.385 μmol/l, OSI: 1.639) (Sevindik et al, 2020 ), O. asterosperma (TOS: 7.548 μmol/l, OSI: 0.221) (Sevindik et al, 2021b ), L. rugatus (TOS: 8.178 μmol/l, OSI: 0.254) (Sevindik, 2020 ), R. stricta (TOS: 8.201 μmol/l, OSI: 0.194) (Krupodorova and Sevindik, 2020 ), and S. granulatus (TOS: 18.933 μmol/l, OSI: 0.603) (Mushtaq et al, 2020 ). The TOS value is an indicator of the total oxidant compounds produced in the fungus, and it shows how much the endogenous oxidants in the fungus are suppressed by the endogenous antioxidants (Gürgen et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The differences among the TAS values for the abovementioned fungus species may be attributed to the potential of these species to produce different antioxidant compounds and the differences in the environments in which they grow. It was also found that the ethanolic extract of H. myxotricha mycelia grown in SDB and GPY media had significantly lower TOS (1.320 μmol/l) and OSI (0.024) values than those for previously studied fungi species such as M. procera (TOS: 6.596 and 10.349 μmol/l, OSI: 0.235 and 0.367) (Akgül et al, 2016 ), O. olearius (TOS: 14.210 μmol/l, OSI: 0.503) (Sevindik et al, 2017 ), A. auricula (TOS: 23.910 μmol/l, OSI: 2.367) , T. versicolor (TOS: 17.760 μmol/l, OSI: 2.166) (Akgül et al, 2017 ), D. quercina (TOS: 6.868 μmol/l, OSI: 2.201) , I. hispidus (TOS: 6.534 μmol/l, OSI: 0.224) , F. fomentarius (TOS: 2.601 μmol/l, OSI: 0.080) , F. torulosa (TOS: 2.969 μmol/l, OSI: 0.074) , T. gibbosa (TOS: 3.522 μmol/l, OSI: 0.597) , T. biforme (TOS: 4.356 μmol/l, OSI: 0.543) (Bal et al, 2017 ), C. unicolor (TOS: 19.308 μmol/l, OSI: 0.288) (Sevindik, 2018b ), G. lividus (TOS: 13.465 μmol/l, OSI: 0.651) (Bal, 2018 ), L. tigrinus (TOS: 19.294 μmol/l, OSI: 1.106) (Sevindik, 2018a ), C. cylindracea (TOS: 21.109 μmol/l, OSI: 0.488) (Sevindik et al, 2018a ), P. limonella (TOS: 4.742 and 33.022 μmol/l, OSI: 0.199 and 1.459) (Sevindik et al, 2018b ), L. sulphureus (TOS: 19.294 μmol/l, OSI: 1.106) (Sevindik et al, 2018c ), C. varius (TOS: 14.358 μmol/l, OSI: 0.627) (Sevindik, 2019 ), C. cibarius (TOS: 6.380 μmol/l, OSI: 0.121) (Sevindik, 2019 a), G. lucidum (TOS: 10.177 μmol/l, OSI: 0.185) (Bal, 2019 ) , L. nuda (TOS: 36.920 μmol/l, OSI: 1.190) (Bal et al, 2019 a), I. geotropa (TOS: 30.385 μmol/l, OSI: 1.639) (Sevindik et al, 2020 ), O. asterosperma (TOS: 7.548 μmol/l, OSI: 0.221) (Sevindik et al, 2021b ), L. rugatus (TOS: 8.178 μmol/l, OSI: 0.254) (Sevindik, 2020 ), R. stricta (TOS: 8.201 μmol/l, OSI: 0.194) (Krupodorova and Sevindik, 2020 ), and S. granulatus (TOS: 18.933 μmol/l, OSI: 0.603) (Mushtaq et al, 2020 ). The TOS value is an indicator of the total oxidant compounds produced in the fungus, and it shows how much the endogenous oxidants in the fungus are suppressed by the endogenous antioxidants (Gürgen et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Production of free radicals in human body by different enzymatic and non-enzymatic processes is very common, which is caused by different factors including environmental and internal body reactions. As a result of these free radicals, oxidative stress is produced in the body cells and this oxidative stress results in advancement and occurrence of so many diseases including cancer, brain and heart diseases (Sevindik et al, 2021). Natural body defense system works to reduce oxidative stress caused by free radicals, but in many cases this natural defense system does not work sufficient to protect body cells.…”
Section: Antioxidant Status Oxidant Status and Oxidative Stress Index...mentioning
confidence: 99%
“…longifolia (L.) HUDSON was determined 3.628 mmol, the TOS capacity 4.046 µmol and the OSI capacity 0.112. 34 The TAS capacity of Euphorbia eriophora BOISS. was determined 5.390 mmol, the TOS capacity 20.971 µmol and the OSI capacity 0.390.…”
Section: Antioxidant Activitymentioning
confidence: 99%